Modified safety techniques for transcatheter repair of superior sinus venosus defects with partial anomalous pulmonary venous drainage using a 100‐mm Optimus‐CVS® covered XXL stent. Issue 5 (22nd February 2022) - Haddad, Raymond N.; Bonnet, Damien; Gewillig, Marc; Malekzadeh‐Milani, Sophie
Abstract: We report the first use of a single 100‐mm long custom‐made version of the Optimus‐CVS® balloon‐expandable PTFE‐covered XXL (15‐Zig) stent (AndraTec, GmbH) to eliminate sinus venosus defect left‐to‐right shunt and redirect anomalous right pulmonary veins blood flow through a new walled channel to the left atrium. Anatomical feasibility and strategy decision were guided by ex‐vivo procedure simulation on the patient‐specific 3D printed heart model and in‐vivo balloon interrogation. Modified procedural and implantation techniques are detailed. Immediate and one‐month follow‐up showed excellent outcomes.